Constructing Studentâ€™s Mathematical Understanding Skills and Self Confidence: Math Game with Visual Basic Application for Microsoft Excel in Learning Phytagoras at Junior High School - Bernard, Martin; Dwi Minarti, Eva; Hutajulu, Masta (International Journal of Engineering and Technology, 2018)
Learning media in Mathematics by using Microsoft Excel software that assisted Visual Basic application is a tool that can be applied for a more interactive visualization so that students better understand about mathematical concepts. Microsoft Excel is a software that serves to process data in the form of numbers that are always associated with mathematical commands. In addition, the functions of commands in Microsoft Excel can be applied in various fields such as Statistics, Economics and Finance, Mathematical Logic, and Engineering. If using mathematical concepts with data processing. But it is not just a number, it can also be used to process objects on shapes or drawings on images. This, of course, requires a function other than the mathematical functions of Visual Basic Applications, which can make math tools more interesting. The advantages of Microsoft Excel with Visual Basic for Application (VBA) are (1) the images are more interactive with different sizes and can make more; (2) more economical; (3)saving time; (4)the software is easy to find, and (5)improving students 'understanding of mathematical concepts and foster students' sense of trust, especially in junior high school students.Â Â